The Strategy Of Marketing Communication Mix To Increase Brand Awareness Through Instagram In PT. ICF - Margareta Ernanda Rahardani; Ridwan Sanjaya (Journal of Management and Business Environment (JMBE), 2022)
PT. ICF is a start-up company in psychological consulting that was established in the midst of a pandemic. In an effort to increase its brand awareness and improve purchase decisions, PT.ICF conducts marketing communication activities (advertising, sales promotion, and public relations and publicity) through social media, especially Instagram. This study aims at determining and analyzing the influence of the marketing communication mix on purchase decisions through the role of brand awareness. In this quantitative descriptive study, 100 respondents were involved through purposive sampling method and 2 key informants comprising CEOs and social media specialists. This study uses tabulation and multiple regression analysis. The result indicates that the comapny’s target market has not been well targeted. Advertising is considered as the best strategy and brand awareness of PT.ICF is on the level of brand recall. Finally, effort to increase brand awareness and purchase decisions is addressed steps that can improve the performance of advertising programs to a maximum.